2019
DOI: 10.5380/rf.v50i1.59103
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTABILITY IN THE PRODUCTIVE PROCESS OF THINNING AND CLEARCUTTING MECHANIZED OPERATIONS IN Pinus taeda L.

Abstract: Some organizations in the Brazilian forestry sector, especially in the activities carried out in forest stands, do not follow the development pace of other industries and the adoption rate of management and quality methodologies and tools. This study aimed to evaluate the predictability of timber harvesting process based on critical points identified in the selective thinning and clear cut operations. Interviews and Pareto chart were used, for the identification and evaluation of the critical points, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This study sought to continue the work carried out in 2016 and later published by Garcia et al (2020), who identified the critical success factors that occur in harvesting operations through three stages: process mapping, identifying and evaluating critical points, and process evaluation. Subsequently, the methodology described by Jacovine et al (1999) was adopted, aiming to determine the variables that influence quality costs in the following categories: prevention, evaluation, and internal and external flaws.…”
Section: Application Of the Qfd Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study sought to continue the work carried out in 2016 and later published by Garcia et al (2020), who identified the critical success factors that occur in harvesting operations through three stages: process mapping, identifying and evaluating critical points, and process evaluation. Subsequently, the methodology described by Jacovine et al (1999) was adopted, aiming to determine the variables that influence quality costs in the following categories: prevention, evaluation, and internal and external flaws.…”
Section: Application Of the Qfd Methodsmentioning
confidence: 99%
“…The elaboration of the quality house sought to evaluate the demands of the customers in order to reduce costs and improve the relationship with external customers (wood processing industry, represented in this research by the company's commercial department) and internal customers (forestry sector, responsible for preparing the area for a new cycle). This set configures the "desired quality", based on the critical success factors pointed out by Garcia et al (2020) (assortments, stump height, trees left in the area) for the two interventions evaluated and damage to the remaining trees in the fourth thinning. Later, customer demands were split into variables that influence quality costs (technical characteristics).…”
Section: Application Of the Qfd Methodsmentioning
confidence: 99%
See 1 more Smart Citation